Forming and automated energy analysis of integrated models of the public buildings and their enclosing structures/Viešosios paskirties pastatų ir jų atitvarų konstrukcijų integruotųjų modelių formavimas ir automatizuota energetinė analizė - Kazakevičiūtė, Gerūta; Cinelis, Gintaris; Kamaitis, Zenonas (Journal of Civil Engineering and Management, 2000)
The problem of energy saving and managing in buildings has become recently more acute. The article concerns the modelling and energy analysis problem of the spatial and structural solutions in newly designed buildings or those under renovation. The results of that task serve as a base for defining thermal indices of the project at different design stages. The core of the developed automated system is formed of integrated graphical digital spatial models of the parts of buildings. These models include different kind of structured geometric and non-geometric (physical, economical) information about the object. The method proposed is based on the open architecture CAD system and operates in the AutoCAD environment. The automated building modelling and energy analysis system consists of such main parts: the subsystem of general geometric modelling of the building or building complex, the subsystem of the geometric modelling of the main building parts and structural components, the subsystem of analysis of models ‘geometry, the subsystem of analysis of models’ energy, the subsystem of the project variants evaluation. Modelling approaches for various design tasks, appropriate parts and the system possibilities are described in the article. According to definite design task intensions different methods were applied to the object. During the approbation the principles put into the system, functional peculiarities, revealed the advantages and disadvantages of it were checked in practice. Two projects were chosen for the experiment (a shop and a school). These objects were different in architectural form, size, number of levels and other parameters. The buildings were modelled by various software tools but, in general, the approbation consisted of two stages: 1. The construction of geometric models and varying of geometric and structural parameters. 2. The energy analysis of integrated geometric models and comparison of the project variants or renovation measures. Specific heat losses and annual consumption of heat energy are used as the main energy-related evaluation indices of the project. An expert (an architect and/or an engineer) has a simple and intuitive tool as a set of operations for geometric transformations and calculation of project indices because the system is provided with modern user interface. It allows the user to work with the building projects operating in one graphical environment. The proposed method could be used by interested experts as a tool for controlling thermal and energy indices at various design stases, searching for rational architectural forms and structural solutions. It takes into account the latest requirements of Lithuanian building regulations concerning heat energy saving. Article in Lithuanian. First Published Online: 26 Jul 2012